Perception of the students in the Early Childhood Education program regarding the dissemination process for the implementation of the redesigned curriculum and transition period during the years 2022-2023.: No aplica (Revista Electrónica Calidad en la Educación Superior, 2024)
This article shows the results of the qualitative analysis of the implementation of the redesign of the study plan and transition period of the Preschool Education Career from the participating students of the different university campuses in the country, in the years 2022-2023. The intention was to communicate the modifications to the curriculum approved in 2020. According to the Self-Assessment Report, 2021, in the Educational Process dimension of the Teaching Development component, the student population showed disagreement with the communication processes of the Career. Among the conclusions, the importance of personalized advice provided by the degree program to students to address students' individual doubts, in addition to establishing clear and precise communication processes, stands out.
Keywords: higher education; academic management; communication strategy; curriculum; self-assessment; accreditation